A Novel GPU-Based Deformation Pipeline. (15th December 2011) - Movania, Muhammad Mobeen; Feng, Lin
Abstract : We present a new deformation pipeline that is independent of the integration solver used and allows fast rendering of deformable soft bodies on the GPU. The proposed method exploits the transform feedback mechanism of the modern GPU to bypass the CPU read-back, thus, reusing the modified positions and/or velocities of the deformable object in a single pass in real time. The whole process is being carried out on the GPU. Prior approaches have resorted to CPU read-back along with the GPGPU mechanism. In contrast, our approach does not require these steps thus saving the GPU bandwidth for other tasks. We describe our algorithm along with implementation details on the modern GPU and finally conclude with a look at the experimental results. We show how easy it is to integrate any existing integration solver into the proposed pipeline by implementing explicit Euler integration in the vertex shader on the GPU.